2020
DOI: 10.1111/jch.14120
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor neprilysin inhibitor as a novel antihypertensive drug: Evidence from Asia and around the globe

Abstract: Hypertension is a worldwide epidemic that continues to grow, with a subset of patients responding poorly to current treatment available. This is especially relevant in Asia, which constitutes 61% of the global population. Hypertension in Asia is a unique entity that is often salt-sensitive, nocturnal, and systolic predominant. Sacubitril/valsartan is a first-in-class angiotensin receptor neprilysin inhibitor that was first used in heart failure with reduced ejection fraction. Sacubitril inhibits neprilysin, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In recent years, due to the emergence of some important new evidence-based medicine for heart failure drugs, the 2021 ESC guidelines ( 47 ) have been updated in this regard, and the status of ARNI has been importantly elevated to become the first-line drug for heart failure treatment, which brings hope for the treatment of heart failure patients. Not only that, several clinical studies in recent years have found that ARNI, represented by sacubitril valsartan, has good therapeutic effects in lowering blood pressure as a new generation drug, and its mechanism of action mainly includes diuretic, natriuretic, vasodilator and anti-sympathetic activity ( 48 53 ). Based on this, the 2020 International Society of Hypertension (ISH) Global Hypertension Practice Guidelines first recommended it as the preferred antihypertensive treatment for heart failure patients, bringing new hope for the treatment of hypertensive patients.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, due to the emergence of some important new evidence-based medicine for heart failure drugs, the 2021 ESC guidelines ( 47 ) have been updated in this regard, and the status of ARNI has been importantly elevated to become the first-line drug for heart failure treatment, which brings hope for the treatment of heart failure patients. Not only that, several clinical studies in recent years have found that ARNI, represented by sacubitril valsartan, has good therapeutic effects in lowering blood pressure as a new generation drug, and its mechanism of action mainly includes diuretic, natriuretic, vasodilator and anti-sympathetic activity ( 48 53 ). Based on this, the 2020 International Society of Hypertension (ISH) Global Hypertension Practice Guidelines first recommended it as the preferred antihypertensive treatment for heart failure patients, bringing new hope for the treatment of hypertensive patients.…”
Section: Resultsmentioning
confidence: 99%
“…[86][87][88][89] Other sodium-excerting drugs such as angiotensin receptor-neprilysin inhibitors (ARNI) and sodium-glucose co-transporter 2 (SGLT2) inhibitors, both of which are proven therapies for heart failure, are also effective in lowering BP. [90][91][92][93][94][95][96][97] SGLT2 inhibitors also decrease 24-hour BP in patients who have both diabetes and hypertension. [98][99][100][101] ARNI have recently been launched for the treatment of hypertension in Japan and China.…”
Section: Choice Of Preferred Antihypertensive Agentsmentioning
confidence: 99%
“…Mineralocorticoid receptor (MR) blockers reduce potassium excrete and hence increase serum potassium, and the recently developed selective MR blocker, esaxerenone, has been shown to reduce nighttime and morning BP, and decrease levels of N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) 86–89 . Other sodium‐excerting drugs such as angiotensin receptor‐neprilysin inhibitors (ARNI) and sodium‐glucose co‐transporter 2 (SGLT2) inhibitors, both of which are proven therapies for heart failure, are also effective in lowering BP 90–97 . SGLT2 inhibitors also decrease 24‐hour BP in patients who have both diabetes and hypertension 98–101 …”
Section: The Hope Asia Network: Seven Action Approaches For Hypertens...mentioning
confidence: 99%
“…79 Accumulating clinical evidence suggests that elderly patients with salt-sensitive hypertension/increased arterial stiffness who are at high risk for developing HF would be ideal candidates for treatment with sacubitril/ valsartan. 77,78,[80][81][82]…”
Section: Angiotensin Receptor Neprilysin Inhibitorsmentioning
confidence: 99%